2020
DOI: 10.3390/biom10091251
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Blockade of Histamine H3 Receptors and Inhibition of Acetylcholine Esterase Alleviate Autistic-Like Behaviors in BTBR T+ tf/J Mouse Model of Autism

Abstract: Autism spectrum disorder (ASD) is a heterogenous neurodevelopmental disorder defined by persistent deficits in social interaction and the presence of patterns of repetitive and restricted behaviors. The central neurotransmitters histamine (HA) and acetylcholine (ACh) play pleiotropic roles in physiological brain functions that include the maintenance of wakefulness, depression, schizophrenia, epilepsy, anxiety and narcolepsy, all of which are found to be comorbid with ASD. Therefore, the palliative effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 79 publications
(140 reference statements)
2
24
0
Order By: Relevance
“…Moreover, systemic administration with the most promising dose of ST-2223 (5 mg/kg), ARP (1 mg/kg) or MEM (5 mg/kg) showed a significant reduction in MDA, as well as a significant elevation in GSH, SOD, and CAT in different areas of the brain. The results observed on the levels of oxidative stress markers are in agreement with several previous reports from our group and other research groups that investigated the effects of H3R antagonists on oxidative stress in the brains of different rodent models [79,[82][83][84][85][86]. Accordingly, previous reports showed that imidazole-based H3R antagonists, including clobenpropit and ciproxifan, mitigated several oxidative stress markers (e.g., MDA and GSH) in amphetamine-or dizocilpine-augmented oxidative stress in a preclinical mouse model of schizophrenia, suggesting the protective effect of H3R antagonists in such disease conditions [87][88][89].…”
Section: In Vivo Mitigating Effects Of St-2223 On Oxidative Stress Insupporting
confidence: 92%
“…Moreover, systemic administration with the most promising dose of ST-2223 (5 mg/kg), ARP (1 mg/kg) or MEM (5 mg/kg) showed a significant reduction in MDA, as well as a significant elevation in GSH, SOD, and CAT in different areas of the brain. The results observed on the levels of oxidative stress markers are in agreement with several previous reports from our group and other research groups that investigated the effects of H3R antagonists on oxidative stress in the brains of different rodent models [79,[82][83][84][85][86]. Accordingly, previous reports showed that imidazole-based H3R antagonists, including clobenpropit and ciproxifan, mitigated several oxidative stress markers (e.g., MDA and GSH) in amphetamine-or dizocilpine-augmented oxidative stress in a preclinical mouse model of schizophrenia, suggesting the protective effect of H3R antagonists in such disease conditions [87][88][89].…”
Section: In Vivo Mitigating Effects Of St-2223 On Oxidative Stress Insupporting
confidence: 92%
“…Three Chamber Paradigm (TCP) TC test was performed according to previously described protocols [48,53,56,57,62,63]. Briefly, the cage consisted of three chambers, wherein the center chamber had two square shaped openings with doors, which provided access to left and right chambers.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…The hippocampus was homogenized in a KCl buffer (Tris-HCl, 10 mM NaCl, 140 mM KCl, 300 mM EDTA, and 0.5% of 1 mM Triton-X-100) at pH 8.0 supplemented with protease and phosphatase inhibitor. The homogenate was centrifuged at 10,000 rcf for 30 min at 4 • C. The supernatant was used according to previously described experimental protocols from our laboratories for the estimation of oxidative stress markers, namely catalase (CAT) and superoxide dismutase (SOD) [48,49,53,56].…”
Section: Biochemical Assessments Brain Tissue Collectionmentioning
confidence: 99%
“…However, other H 3 receptor antagonists/inverse agonists are in development for other indications relevant to those with NDDs. Most these have focused on the modulating restricted and repetitive behaviors or aggression or at improving cognition and sociability in animal models (Orsetti et al, 2001;Galici et al, 2009;Southam et al, 2009;Esbenshade et al, 2012;Brown et al, 2013;Baronio et al, 2015;Eissa et al, 2018aEissa et al, ,b, 2020b. For example, a clinical trial with the H 3 receptor antagonist, AZD5213, for people with TS showed a 2-3 point reduction in Total Tic Severity Score Compared to placebo (Clinical Trials.Gov, 2016).…”
Section: H 3 Receptor Antagonistsmentioning
confidence: 99%